THE SUSTAINABLE COMPETITIVENESS OF NATURE-BASED TOURISM FROM THE TOURIST PERSPECTIVE ASSESSMENT - Ine Rahmadania Saldianovitta; Risna Wijayanti; Nur Prima Waluyowati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
This research aims to examine aspects of the competitiveness of natural tourist destinations, including eco-destination image, ecotourism experience, and destination quality so that they can contribute to environmental conservation efforts, sustainable use of natural resources, and determining strategies for managers of natural tourist destinations to improve quality. Moreover, the attractiveness of the tourist destinations it manages. Quantitative research collects, analyzes, and displays data numerically using empirical studies. Used in this research. A survey via questionnaire with closed questions was conducted at three natural tourist destinations in Batu City, namely Selecta Tourism, Jatim Park II, and Batu Love Garden. As a result, the respondents generally have good expectations for tourist destinations in Batu City regarding the eco-destination experience, image variables, and destination quality variables. However, in the Destination Quality variable, the amenities indicator, most respondents do not fully agree with access for people with disabilities and pregnant women and medical facilities around tourist destinations. So, the results of this research can be used as a review and evaluation for tourist destination managers and local governments regarding these facilities.